2023
DOI: 10.1371/journal.pone.0282036
|View full text |Cite
|
Sign up to set email alerts
|

Self-management of multiple long-term conditions: A systematic review of the barriers and facilitators amongst people experiencing socioeconomic deprivation

Abstract: Background Multiple long-term conditions are rising across all groups but people experiencing socioeconomic deprivation are found to have a higher prevalence. Self-management strategies are a vital part of healthcare for people with long-term conditions and effective strategies are associated with improved health outcomes in a variety of health conditions. The management of multiple long-term conditions are, however, less effective in people experiencing socioeconomic deprivation, leaving them more at risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Health literacy refers to a person's ability to access, understand and use information to make decisions about their health 27 . Low health literacy results in challenges around making informed decisions about health and has the potential to reinforce existing health inequalities 6 . Low health literacy was evident amongst participants, alongside low financial literacy; the latter being a life skill highly related to the well‐being of individuals and crucial to financial inclusion 8,28 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Health literacy refers to a person's ability to access, understand and use information to make decisions about their health 27 . Low health literacy results in challenges around making informed decisions about health and has the potential to reinforce existing health inequalities 6 . Low health literacy was evident amongst participants, alongside low financial literacy; the latter being a life skill highly related to the well‐being of individuals and crucial to financial inclusion 8,28 .…”
Section: Discussionmentioning
confidence: 99%
“…16 A systematic review conducted by the authors found that aspects in people's lives that can facilitate self-management include; opportunities to maintain independence, being in paid employment, receiving informal support from family and peer networks, engaging in physical activity and eating a healthy diet. 6 In a further systematic review focused on self-management interventions tailored for people experiencing socioeconomic deprivation, the trials on MLTCs showed promise in improving outcomes but have not been adopted into practice, suggesting implementation barriers. 17 The most effective tailoring of self-management interventions included adaptions for low literacy, the involvement of community health workers or peer leaders, providing helpful materials if needed and financial incentives.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations